The Relationship Between Breast Care and Breast Milk Production in Postpartum Mothers at PMB Khoiruzan Talang Padang Tanggamus in 2022 - Diantina, Hera; Simanjuntak, Farida M; Anggraini, Ani; Marbun, Vermona; Silitonga, Riris Octryna (Jurnal Ayurveda Medistra, 2025)
Background: The low rate of exclusive breastfeeding will impact the quality and survival of future generations. Globally, in 2019, 144 million children under five were estimated to experience stunting. Breast care is the practice of taking care of the breasts to ensure smooth breastfeeding and to prevent common issues that arise during nursing. Research Objective: To determine the relationship between breast care and breast milk production in postpartum mothers at PMB Khoiruzan Talang Padang Tanggamus in 2022. Research Method: This study used a quantitative research design. The population in this study consisted of 30 postpartum and breastfeeding mothers at PMB Khoiruzan Talang Padang Tanggamus in 2022. The sampling technique used was total sampling, so the total number of samples in this study was 30 respondents. Statistical testing used the chi-square test. Research Results: Univariate analysis showed that 26 respondents (86.7%) practiced breast care, and 21 respondents (70.0%) had adequate breast milk production. Bivariate analysis revealed a relationship between breast care and milk production, with a p-value of 0.005. Conclusion: There is a relationship between breast care and breast milk production.